Intimate Partner Violence Identification and Response: Time for a Change in Strategy - Rhodes, Karin V. (Springer-Verlag, 2011)
BACKGROUND: While victims of intimate partner violence (IPV) present to health care settings for a variety of complaints; rates and predictors of case identification and intervention are unknown. OBJECTIVE: Examine emergency department (ED) case finding and response within a known population of abused women. DESIGN: Retrospective longitudinal cohort study. SUBJECTS: Police-involved female victims of IPV in a semi-rural Midwestern county. MAIN MEASURES: We linked police, prosecutor, and medical record data to examine characteristics of ED identification and response from 1999–2002; bivariate analyses and logistic regression analyses accounted for the nesting of subjects’ with multiple visits. RESULTS: IPV victims (N = 993) generated 3,426 IPV-related police incidents (mean 3.61, median 3, range 1–17) over the 4-year study period; 785 (79%) generated 4,306 ED visits (mean 7.17, median 5, range 1–87), which occurred after the date of a documented IPV assault. Only 384 (9%) ED visits occurred within a week of a police-reported IPV incident. IPV identification in the ED was associated with higher violence severity, being childless and underinsured, more police incidents (mean: 4.2 vs 3.3), and more ED visits (mean: 10.6 vs 5.5) over the 4 years. The majority of ED visits occurring after a documented IPV incident were for medical complaints (3,378, 78.4%), and 72% of this cohort were never identified as victims of abuse. IPV identification was associated with the day of a police incident, transportation by police, self-disclosure of “domestic assault,” and chart documentation of mental health and substance abuse issues. When IPV was identified, ED staff provided legally useful documentation (86%), police contact (50%), and social worker involvement (45%), but only assessed safety in 33% of the women and referred them to victim services 25% of the time. CONCLUSION: The majority of police-identified IPV victims frequently use the ED for health care, but are unlikely to be identified or receive any intervention in that setting.